2021
DOI: 10.1021/acsami.1c10805
|View full text |Cite
|
Sign up to set email alerts
|

NiWO4 Microflowers on Multi-Walled Carbon Nanotubes for High-Performance NH3 Detection

Abstract: NiWO4 microflowers with a large surface area up to 79.77 m2·g–1 are synthesized in situ via a facile coprecipitation method. The NiWO4 microflowers are further decorated with multi-walled carbon nanotubes (MWCNTs) and assembled to form composites for NH3 detection. The as-fabricated composite exhibits an excellent NH3 sensing response/recovery time (53 s/177 s) at a temperature of 460 °C, which is a 10-fold enhancement compared to that of pristine NiWO4. It also demonstrates a low detection limit of 50 ppm; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…Further, CNTs have a significant specific surface area, a hollow structure, and unique electrical properties, making them an attractive one-dimensional nanomaterial for sensors, especially for gas detection. Previous reports have shown that modifying the semiconducting characteristics of TMDCs through the decoration of carbon nanotubes can achieve the desired sensitivity and selectivity for VOC detection. …”
Section: Introductionmentioning
confidence: 99%
“…Further, CNTs have a significant specific surface area, a hollow structure, and unique electrical properties, making them an attractive one-dimensional nanomaterial for sensors, especially for gas detection. Previous reports have shown that modifying the semiconducting characteristics of TMDCs through the decoration of carbon nanotubes can achieve the desired sensitivity and selectivity for VOC detection. …”
Section: Introductionmentioning
confidence: 99%
“…However, combining these materials needs a complicated process to optimize their morphology and structure. Also, the resistance and operating temperature of the devices were typically increasing so that they lost the merits of CNTs. Introducing nanoparticles or control of surface energy and morphology in the supporting substrate has been applied to increase the adsorption of target gas molecules for enhanced gas response. In addition, attaching functional groups onto the CNTs by defect engineering can increase their binding affinity with target gas molecules . However, the functionalization, such as oxidation, inevitably decreases the electrical properties of CNTs, which is undesirable for sensor response.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor's responses become stabilized over time, proving the 1T′/2H sensor's long‐term stability. Figure 4f compares the NH 3 sensing results of the 1T′/2H/1T′ sensor with those from recent representative NH 3 sensors made of Ti 3 C 2 T x, [ 30 ] SnO 2 nanoparticles, [ 31 ] MoS 2 /MoO 3, [ 32 ] MoS 2, [ 33 ] NiWO 4 /CNT, [ 34 ] WS 2, [ 35 ] M‐CNTs, [ 36 ] Cs 3 Bi 2 I 6 Br 3, [ 37 ] and RGO/CuO. [ 38 ] The detection limit and operating current of our 1T′/2H/1T′ sensor outperform most of these NH 3 sensors.…”
Section: Resultsmentioning
confidence: 99%